Relationship Between Various Cement Mixture, Cement Fixation and Gait Study for Total Hip Replacement Via Finite Element Analysis (FEA) - Shuib, Solehuddin; Romli, Ahmad Zafir; Mohd Arrif, Iffa; Hamizan, Najwa Syakirah; Saeid, Nawaf Hazim (International Journal of Integrated Engineering, 2023)
To secure the total hip replacement (THR) components, introduced in the 1960s, polymethyl methacrylate (PMMA) bone cement was used as a fixation. The cement polymerizes and becomes firm to hold the implant in place. However, the failure of cement in total hip replacement may lead to hip fractures and dislocations which is detrimental to the patient’s well-being whether in the short-term or long-term. Hence, the aim of this study is to find suitable cement mixtures for total hip replacement compromising of Young Modulus of 2.24 GPa, 0.3129 GPa, 0.03394 GPa and 0.07961 GPa, as reported from prior research. Three separate sorts of proximal cemented techniques were used to deposit the PMMA cement: 40 mm cement reduction, 80 mm cement reduction and full cement (datum). The Titanium Ti-6A1-4V (Ti-41) Charnley hip implant stem model with a Young Modulus of 100 GPa and a Poisson’s ratio of 0.3 was applied in the ANSYS Workbench 2020 R2 software to be analyzed with the three different proximal cemented approaches for each cement mixtures. Subsequently, the total deformation and von Mises stress were simulated under various loading circumstances, including standing, walking, stair climbing and falling. Nevertheless, as shown in the results obtained, all the hip implants consider safe because their von Mises stress does not exceed the yield strength of Titanium Ti-6A1-4V, which is 0.88 GPa. Finally, it may be concluded that, in comparison to the full cement (datum) and 80 mm cement reduction with Young Modulus of 2.24 GPa, 0.3129 GPa, 0.03394 GPa and 0.07961 GPa, the most improvement in the context of total deformation and von Mises stress is the 40 mm cement reduction with Young Modulus of 2.24 GPa.